ANALISIS STRENGTHS WEAKNESSES OPPORTUNITIES THREATS (SWOT) POLA TANGGUNG RENTENG DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH (KSPPS) BAYTUL IKHTIAR CABANG LEUWISADENG - Iman Afriansyah; Ria Kusumaningrum; Muhamad Rizal (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
Sharia financing jointly and severally is one of the strategies of Islamic financial institutions in channeling third party funds. This study aims to analyze the effectiveness of sharia financing jointly and severally. Researchers used a SWOT analysis tool (Strengths, Weaknesses Opportunities, and Threats). The method in this research is qualitative research, observation, and interviews. The results of this study indicate that sharia financing jointly and severally implemented by the Baytul Ikhtiar Savings and Loans and Sharia Financing Cooperative (KSPPS) is very effective and good. This began with a fairly rigorous selection process for recruiting prospective members for joint responsibility financing, then intensive mentoring or monitoring was carried out by KSPPS Baytul Ikhtiar. There are fewer problem financing, and sharia financing jointly and severally can still be carried out at KSPPS Baytul Ikhtiar.